Nasrul Arif Zakaria Puspanita Community Care Award recipient - UMP, PNC (2019)
Time management is the key to the success for Pahang-born Nasrul Arif Zakaria, 23, Bachelor of Computer Science (Software Engineering) with Honours who holds the Dean's Award every semester.